Dendrimer crown-ether tethered multi-wall carbon nanotubes support methyltrioxorhenium in the selective oxidation of olefins to epoxides. Issue 29 (1st May 2020) - Bizzarri, Bruno Mattia; Fanelli, Angelica; Botta, Lorenzo; Sadun, Claudia; Gontrani, Lorenzo; Ferella, Francesco; Crucianelli, Marcello; Saladino, Raffaele
Abstract : Benzo-15-crown-5 ether supported on multi-wall carbon nanotubes (MWCNTs) by tethered poly(amidoamine) (PAMAM) dendrimers efficiently coordinated methyltrioxorhenium in the selective oxidation of olefins to epoxides. Abstract : Benzo-15-crown-5 ether supported on multi-wall carbon nanotubes (MWCNTs) by tethered poly(amidoamine) (PAMAM) dendrimers efficiently coordinated methyltrioxorhenium in the selective oxidation of olefins to epoxides. Environmentally friendly hydrogen peroxide was used as a primary oxidant. Up to first and second generation dendrimer aggregates were prepared by applying a divergent PAMAM methodology. FT-IR, XRD and ICP-MS analyses confirmed the effective coordination of methyltrioxorhenium by the benzo-15-crown-5 ether moiety after immobilization on MWCNTs. The novel catalysts converted olefins to the corresponding epoxides in high yield without the use of Lewis base additives, or anhydrous hydrogen peroxide, the catalyst being stable for more than six oxidative runs. In the absence of the PAMAM structure, the synthesis of diols largely prevailed.